INHIBITORY EFFECT OF HESPERIDIN ON VOLUNTARY ETHANOL DRINKING AND PREFERENCE IN SWISS ALBINO MICE - KRUSHNA KASHINATHRAO ZAMBARE; KAILASAM KOUMARAVELOU (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This investigation is expected to evaluate the potential of hesperidin in inhibiting ethanol (EtOH)-induced behavioral sensitization and its effect on voluntary EtOH consumption and preference in Swiss albino mice. Methods: Behavioral sensitization was induced using EtOH (2 g/kg), and the voluntary EtOH drinking preference test was employed to assess the effects of hesperidin. Mice were treated with hesperidin at doses of 4, 8, and 16 mg/kg (oral), and changes in EtOH intake and preference were recorded. Results: Hesperidin significantly reduced EtOH consumption in rats at doses of 8 mg/kg and 16 mg/kg (p<0.001), with effects observed from days 31 to 34. Acute dosing at 4 mg/kg also decreased EtOH intake (p<0.001). Ondansetron showed similar efficacy (p<0.001). No significant group differences were found during the restricted access phase. Furthermore, no significant changes in water intake were observed during the restriction (days 19–28) or treatment phases (days 29–34; p>0.05), with hesperidin (4–16 mg/kg) and ondansetron (4 mg/kg) showing no effect (two-way repeated measures analysis of variance). Conclusion: Hesperidin effectively attenuates EtOH -induced behavioral sensitization as well as reduces the rewarding effects of EtOH, suggesting its potential as a natural therapeutic agent for managing alcohol-related illnesses.